Apollo APA: Towards a Model to Care of People with Hearing Impairment in Smart Environments - Tavares, João E. da R.; Guterres, Tefferson D. da R.; Barbosa, Jorge L. V. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
In Brazil, there are more than 9.3 million People with Hearing Impairment (PWHI) and deaf who face daily accessibility difficulties. On the other hand, there is the growth of the use of mobile devices and the application of the Internet of Things (IoT). The motivation for the development of this work lies in the absence of user interface systems based on sign language and customizable according to the profile that is applied to the prevention of risks external to the health of the deaf. This paper proposes the Apollo APA (Auditive Personal Assistant) model, which promotes accessibility for PWHI and deaf people in a smart home environment, especially regarding security. The scientific contribution of Apollo APA lies in the detection of ambient risks using neural networks via machine learning with supervised training. Besides this, the model APA also considers the user profile, mainly the degree of deafness, to generate accessible notifications represented in Brazilian Sign Language (LIBRAS in Portuguese). The notifications of risk sent to the smartphone of PWHI or deaf also can vibrate or turn on the light of the device. We implemented a prototype of a smart home that collects environmental sounds and notifies the deaf user. The scenario-based assessment included 3 activities of daily living (ADL) events of a deaf user: a kettle boiling over the stove, a dog barking and one person knocking on the door. The results indicate the means of the f-score of 0.73. Usability and acceptance evaluations were performed by 2 deaf users in a real setting. The results indicate the approval of 87% in the perceived ease of use and 100% in the perceived utility.